The hungry coat : a tale from Turkey - Demi. (New York : Margaret K. McElderry Books, 2004)
After being forced to change to a fancy new coat to attend a party, Nasrettin Hoca tries to feed his dinner to the coat, reasoning that it was the coat that was the invited guest.
Book Links (A.L.A.).
School Library Journal starred.
Wilson's Children.
4.6.
4.6
K-3
Keywords: Folklore -- Turkey; Nasreddin Hoca (Legendary character) -- Juvenile literature; Folklore -- Turkey; Nasreddin Hoca (Legendary character); Folklore -- Turkey; Nasreddin Hoca (Legendary character)